The Use Of Voice in Opac Using Google API Voice Recognition & Speech Synthesis and Fullproof Algorithm as Faster Searching Device - Suadaa Irfana, Maisyatus; ., . (International Journal of Engineering and Technology, 2018)
The development of technology provides convenience to all human beings including public librarians. OPAC becomes a solution for library users to search books in a short time with accurate data in which they previously used a manual system. However, there are some users, especially users with certain disabilities, such as users who cannot see, are unable to use OPAC. The idea came up to make OPAC with voice as a substitute for another alternative of text input use. OPAC with voice has been used in several big libraries in Indonesia. One of them is in State Islamic University of Sunan Kalijogo.Â  However, because there are still some shortcomings in terms of voice recognition in which one of them is the limited number of recognizable languages, so in this study, it will be discussed the use of Google API for voice recognition and voice synthesis which is then integrated with OPAC, and the algorithm used in the search is Fullproof algorithm. The methods used in this research were literature study, system design, prototype application creation, and application testing. From the test results, the application is able to search the data book in OPAC using voice input from various languages with a relatively fast searching time. Applications are also able to voice the book found in the form of sound.Â